Is rotator cuff repair worthwhile in patients with co-morbidities? - Shah, Yash Kishore; Khavte, Rohan Kiran; Munshi, Parag Kishore (International Journal of Research in Medical Sciences, 2017)
Background: Rotator cuff tears are a common source of shoulder pain. The incidence increases with age and is most frequently due to degeneration of the tendon, rather than injury. This study is done to see whether in patients having established rotator cuff tears with co-morbidities like hypertension diabetes, epilepsy, etc. a surgical repair is worthwhile or whether it is better to leave such patients alone in order to give them a better quality of life. Methods: A total of 35 patients with co-morbidities, treated by a single surgeon of which 8 by open method, 19 with arthroscopic assisted mini open rotator cuff repair and 8 entire arthroscopically were evaluated retrospectively. Small tears (<1 cm), medium tears (1-3 cm); large tears (3-5 cm) were addressed by the same surgical procedure using bone tunnels, suture anchors, or a combination of both. The patients were evaluated by history, examination, pain scores and constant scores. Results: As compared to patients with no co-morbidities, these patients took longer time for healing especially diabetics. Despite that 27 patients had excellent pain relief, 5 good and 3 poor pain relief. Constant scores improved in all patients. Conclusion: Patients with co-morbidities take longer time to heal, yet the final outcome which is attained and relief of pain and relief in the form of activities of daily living that we could offer the patients makes the surgery worthwhile. It is well worth operating on patients with co-morbidities and a rotator cuff tear, giving them a better pain free life and better activities of daily living.